PERTANGGUNG JAWABAN PT. GRAB INDONESIA TERHADAP PENGEMUDI YANG MENDAPAT ORDER FIKTIF - Yenni Aurelia Marpaung (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
Currently in Indonesia, one of the businesses is a rapidly growing business that is using the utilization of technology as a container. Entrepreneurs began to develop as well as compete to improve their business in innovation and creativity by the way of the utilization of technology as a means of business in accordance with the increasing needs of the community and ease in daily activitiesOne of the businesses that uses the utilization of technology is the application Grab, Grab is one of the platform services on demand, which is headquartered in Singapore. This app offers many choices of transport services ranging from taxis, private cars, motorcycles, food ordering, to delivery packages to meet the needs of passengers. But with financing through the cash there is one of the consequences of the transaction GrabFood where the occurrence order is fictitiousThe author using a case study approach which includes accountability for the PT. Grab Indonesia against the driver Grab that become victims to orders fictitious according to the law of consumer protection and the law a civil contract and using the theory of accountability